Determinants of the Risk Tolerance of Individual Investors - ., Rahmawati; Kumar, M. Dileep; Kambuaya, Meyland; Jamil, Farhan; Muneer, Saqib (International Journal of Economics and Financial Issues, 2015)
This study presents new evidence on determinants of risk tolerance of individual investors of Pakistan. The main objective of the research is to evaluate the factors that determine the individuals' decisions. It is essential to understand the factors of risk tolerance and how to manage these factors to enhance the ability of risk tolerance in making investment decisions and increasing economic growth. The survey instrument used to investigate the determinants of risk tolerance is based on a questionnaire developed by Dow Jones and Company in 1998 that is in Bodie et al. (2007). The questionnaire contains two parts. The first part includes demographic information about and second part includes questions or cases, while univariate analysis is used to calculate the significance of the results. Four hypotheses have been formulated and tested. Relying on the results of the study, the author concludes that men are less risk averse then women, educated investors are more likely to take risk, less wealthy investors are less risk tolerant then wealthy investors and the interesting fact found is that there is no as such strong relation between age and the level of individual risk tolerance although the risk tolerance of each age group is significantly different. Education and wealth are highly correlated with risk tolerance. Improving the level of education to make investors more risk tolerant towards risky investments of higher gains, understand the factor of gender to find the reason why women are less risk tolerant then men, and why they are not contributing in the economic growth of the country, don't treat investors as a homogeneous group, whether they should consider men and women as a separate market groups, each group has its own requirements and strategies. The results also support the importance of proper training programs for risk assessment, acceptance and management should be conducted in order to design risk accepting behavior of the individuals in a useful way. This research would be significant for the investors to enhance their investment decisions in a risky situation. This research would also be helpful for the financial institutions, investment companies, Government, NGOs and social activist in treating the investors in such a way so that their risk tolerance ability can be increased which in return contribute in economic growth. Keywords: Risk Tolerance, Gender Differences, Target Market, Investment Programs JEL Classification: G32